Activity of Cytochrome P450 Monooxygenase (CYPs) Metabolic Enzymes as Markers of Insecticide Resistance in Anopheles vagus Muara Enim Mosquitoes, Indonesia - Dalilah; Muhaimin Ramdja; Dwi Handayani; Lasbudi P Ambarita; R. Irpan Pahlepi; Ahmad Ghiffari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
The use of synthetic pyrethroids in insecticide-treated bed nets (LLINs) and spray form (IRS) has been carried out since 2012 in Muara Emil Village and since 2016 in all villages in Tanjung Agung District, Muara Enim Regency. Biochemical resistance can occur to the enzymes that play a role in detoxifying the insecticide. This study aims to identify whether there is an increase in the levels of the enzyme Cytochrome P450 monooxygenase (CYPs) through the enzyme biochemical test on the malaria vector mosquito Anopheles vagus originating from Pagar Dewa Village and Muara Emil Village, Muara Enim Regency. The sample of female Anopheles mosquitoes was not full. Blood was taken at night using the resting collection method. Mosquitoes that have been identified as Anopheles vagus species are used to check CYPs enzyme levels using the ELISA method. The results of the biochemical test showed that enzyme levels increased from the Muara emil and Pagar Dewa village mosquitoes with a percentage of 71% and 61.53% (with cut off point OD> 0.165). The value of CYPs enzyme levels for mosquitoes from Muara Emil village was higher than that of the mosquitoes from Pagar Dewa Village (mean 0.005027 ± 0.007). The increased activity of the CYPs enzyme plays a role in the detoxification of synthetic pyrethroid insecticides that can cause resistance. The high levels of enzymes from the villages of Muara Emil and Desa Farah Dewa are in line with intensive insecticide exposure in eradicating malaria vectors in the highest malaria transmission areas in Muara Enim Regency.